MODEL PENINGKATAN KINERJA MANAJERIAL DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING (Studi Pada Kantor Kecamatan di Kota Semarang - Nurul Latifah Pancawardani; Panca Wahyuningsih (BBM (Buletin Bisnis & Manajemen), 2017)
This research is motivated by the issue or phenomenon in which there are some users of public services government agency (district office-red) are still lacking memuasakan, for example, the existence; management of e-KTP, Legalization, SKCK, Letter Move etc. and laments of society due to information management systems and bureaucracy have not been so inadequate, so the lack of speed and accuracy in their handling of the case is. If this is the case can be indicated that the district office managerial performance to the public yet and or less common memadai.Secara aims to analyze the influence of emotional intelligence and spiritual intelligence on managerial performance to organizational culture as an intervening variable. So it can be analyzed whether variable organizational culture can serve as a mediation (intervening) to managerial performance. Specifically to improve managerial performance in public service district office in the city, with good emotional intelligence and spiritual intelligence of the employees adequate districts its output will be more significant managerial performance.The variables in this study consisted of four variables which in the first stage variables emotional intelligence and spiritual intelligence become independent variable while organizational culture becomes the dependent variable. Then in the second stage of emotional intelligence and spiritual intelligence as an independent variable, organizational culture as an intervening variable, while variables managerial performance as the dependent variable.Research data collection techniques by spreading questionnaires to employees (management) district office in the city of Semarang are arranged systematically with multiple choice answers are easy to understand. Distribution of questionnaires by way of a direct encounter conducted in the period April to August 2015, with the number of samples of 174 respondents. Then the data collected through a questionnaire to test the data analyst; validity and reliability, followed by analysis of the path (Path Analysis), test the strength of the model using SEM (Structural Equation Modelling).Keywords: Emotional Intelligence, Spiritual Intelligence, Organizational Culture and Managerial Performance.